Tindak Tutur Memuji Bahasa Jepang di Kalangan Wanita Jepang - Susanti, Rita; Siregar, Maduma (Bina Nusantara University, 2010)
The aim of this research is to discover the type, form, and function of Japanese woman in using compliments. Data is taken from the manga Cardcaptor Sakura volume 3 to 5, written by CLAMP manga writer group. Analysis found several types of compliment found in and the form of compliment used are adjectives. The reason Japanese woman give compliment to others is to express an admiration of something positive that belongs to the listener. Â